PENGARUH PENERAPAN MODUL QURAN HADIST TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS X MA ISLAMIYAH KEPUNG KEDIRI - Dian Kusuma Wardani; Ramadania Fitri Rawinda; Hilyah Ashoumi (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2021)
This study aims to determine the application of the Qur'an Hadith module to the students of class X MA Islamiyah Bulurejo Kepung Kediri and the effect of using the Koran Hadith module on the learning outcomes of class X students at MA Islamiyah Bulurejo Kepung Kediri. The population in this study were students of class X MA Islamiyah with a total of 30 students. Data collection methods used are test and observation. The data normality test states that the data spreads following a normal distribution so that the paired t test can be used in this study. The results of the paired t-test hypothesis testing showed a significant value (0.000) < alpha (0.05), so it can be said that there is a significant effect of using the Quran Hadith module on student learning outcomes. The results of the calculation of the average posttest score are better, namely 86.67 compared to the pretest average value, which is 77.67. So it can be said that the use of modules can be a solution in teaching and learning activities to help students more easily understand the material presented by the teacher.